2021
DOI: 10.1186/s12876-021-02051-6
|View full text |Cite
|
Sign up to set email alerts
|

Three-step operation for esophago-left bronchial fistula with respiratory failure after esophagectomy: a case report with literature review

Abstract: Background The development of esophago-bronchial fistula after esophagectomy and reconstruction using a posterior mediastinal gastric tube remains a rare complication associated with a high rate of mortality. Case presentation A 63-year-old man with esophageal cancer underwent a thoracoscopic esophagectomy with two-field lymph node dissection and reconstruction via a gastric tube through the posterior mediastinal route. Postoperatively, the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In recent years, with the development of minimally invasive medical technology, thoracoscopic surgery has been increasingly used in clinical practice. Video-assisted thoracoscopic lobectomy features significant advantages such as minimally invasive and mild pain, which can effectively shorten the hospital stay of patients [ 7 ] and reduce the incidence of postoperative complications. The National Comprehensive Cancer Network guidelines (NCCN) recommended thoracoscopic lobectomy as the standard surgical approach for the treatment of lung cancer in 2006 in light of its remarkable efficacy [ 8 ], and in the previous decade, different branches of the technique were developed from the previous four-port and three-port surgical approaches to the two-port and single-port ones.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the development of minimally invasive medical technology, thoracoscopic surgery has been increasingly used in clinical practice. Video-assisted thoracoscopic lobectomy features significant advantages such as minimally invasive and mild pain, which can effectively shorten the hospital stay of patients [ 7 ] and reduce the incidence of postoperative complications. The National Comprehensive Cancer Network guidelines (NCCN) recommended thoracoscopic lobectomy as the standard surgical approach for the treatment of lung cancer in 2006 in light of its remarkable efficacy [ 8 ], and in the previous decade, different branches of the technique were developed from the previous four-port and three-port surgical approaches to the two-port and single-port ones.…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal stents and airway-esophageal double stents are often selected for TEF, especially to close the stula and improve the quality of life. [11,12] Although there are reports of improved survival, [13,14] it is considered to be a palliative treatment, and associated disadvantages include the possibility of stula enlargement and di culty in surgical manipulation due to stenting. Surgical treatment may be an option, but most patients undergo esophageal bypass surgery [15,16] or muscle ap coverage [9,17] as a palliative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A pedicled subcutaneous fascia flap wrapping the trachea has been reported in the literature for TGTF, [2] but the mortality rate is higher, up to 64.3%. Sato [9] reported that the use of a 3-step surgery could be an effective procedure for TGTF. Above all, there have been no reports on the successful treatment of patients with TGN associated with TGTF during staged esophageal surgery.…”
Section: Discussionmentioning
confidence: 99%